Islamic Public Finance: Productive Zakat and Taxes As Instruments of The Country's Economy - Zahra Maulida, Atika; Purnomo, Agus (Nuban Jagadhita Centre, 2023)
Purpose: This research aims to determine productive zakat and taxes in the management and distribution of funds for economic activities, education, health, and infrastructure. Zakat and taxes are instruments of income obtained by the community that must be spent based on the provisions stipulated in the Al-Quran and Hadith, while taxes are instruments of state income collected from the community from income tax, land, and building tax, value-added tax, income tax, and others. Methodology: The research method in this study uses a qualitative method with a descriptive approach using interview data and report data on the collection and distribution of productive zakat funds and taxes for the country's economic growth. This research data was collected using structured interviews regarding the collection and distribution of funds in economic activities, education, health, and infrastructure to provincial BAZNAS staff and South Kalimantan provincial tax staff. Findings: There are findings in research conducted by researchers that the contribution of productive zakat funds and taxes distributed in economic activities, education, health, and infrastructure development has an impact on regional economic growth of 56% from 2022-2023, and while the instrument is equal to 87 %.